Gereja di Mata dan di Hati: Eskplorasi Antara Bentuk dan Esensi - Desti Meliana Mangngi; Aprianus Lendrik Moimau (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
This article examines in depth the relationship between the outward form and the spiritual essence of the Church in the context of contemporary Christianity. The church is not only understood as a physical structure with buildings, organizational systems, and orderly worship, but also as a spiritual community that reflects the love of Christ, the presence of God, and a missiological calling in the world. An imbalance between external aspects and spiritual substance can lead to disorientation of church functions, both in the aspect of service and in the meaning of the faith of the people. Excessive focus on form can make the church spiritually dry, while neglect of order and form can lead to chaos in church life. Through a qualitative approach with a literature study method, this article examines the thoughts of several theological figures such as Miroslav Volf, who emphasizes the church as a reflection of the Trinitarian relationship; Lesslie Newbigin, who offers the perspective of the church as an institution, community of the word, and communion of the Spirit; and Stephen Suleeman, who highlights the role of the church as an agent of social and spiritual transformation in Indonesia. The research also considers contemporary challenges, such as the development of digital technology, shifting social values, and the declining interest of younger generations in formal religious institutions. Therefore, this article emphasizes the importance of maintaining a balance between the form and essence of the church in order to remain relevant, contextual, and faithful to the faith.